P-glycoprotein- and mrp2-mediated octreotide transport in renal proximal tubule - Gutmann, Heike; Fricker, Gert (British journal of pharmacology, 2000)
Transepithelial transport of a fluorescent derivative of octreotide (NBD-octreotide) was studied in freshly isolated, functionally intact renal proximal tubules from killifish (Fundulus heteroclitus). Drug accumulation in the tubular lumen was visualized by means of confocal microscopy and was measured by image analysis. Secretion of NBD-octreotide into the tubular lumen was demonstrated and exhibited the all characteristics of specific and energy-dependent transport. Steady state luminal fluorescence averaged about five times cellular fluorescence and was reduced to cellular levels when metabolism was inhibited by NaCN. NBD-octreotide secretion was inhibited in a concentration-dependent manner by unlabelled octreotide, verapamil and leukotriene C4 (LTC4). Conversely, unlabelled octreotide reduced in a concentration dependent manner the p-glycoprotein (Pgp)-mediated secretion of a fluorescent cyclosporin A derivative (NBDL-CS) and the mrp2-mediated secretion of fluorescein methotrexate (FL-MTX). This inhibition was not due to impaired metabolism or toxicity since octreotide had no influence on the active transport of fluorescein (FL), a substrate for the classical renal organic anion transport system. The data are consistent with octreotide being transported across the brush border membrane of proximal kidney tubules by both Pgp and mrp2.
Gesehen am 26.04.2017